Modeling of the photocatalytic reactor for blue wastewater degradation by a composite based on zinc oxide, green pigments, and phenolic resins. - Olivo Alanís, Daniel Simón (2019)
n this research, an extension of the kinetic and quantum yield model, as well as the evaluation of the radiation absorption phenomena on a visible-LED reactor for the photocatalytic blue wastewater degradation employing a novel polymeric material as a photocatalyst was proposed. Three novel materials based on phenolic resins were developed, and further characterized by electronic and optical techniques. The polymeric semiconductors were evaluated for the photocatalytic degradation of methylene blue, as well as for the synthetic blue wastewater treatment. The proposed kinetic model, for further reactor design, takes into account the generation of electron-hole pair and the reactive oxygen species via redox reactions, as well as the attack of the reactive species to the pollutant. Also, the mechanistic contribution of the different operational conditions was studied with the novel proposed effective photocatalytic mechanism model. The proposed models were validated under several operation conditions to evaluate its robustness